IT Governance Modes Choice: An Institutional Theory Perspective - Karim Ben Boubaker; Saida Harguem; Mari Nyrhinen (International Journal of Management and Data Analytics)
This study explains IT Governance modes’ choice in organizations using institutional theory. A conceptual framework is developed, and several propositions are presented. By adopting a  non-rational perspective, a case study is conducted in the Canadian public sector. The results show that the three different IT Governance modes - centralized, decentralized, and federal - meet the requirements of process and property variables and can thus be considered legitimized institutions. Also, institutional pressures are found to play an important role in determining the chosen IT Governance mode. Coercive pressures exerted by the organization's legal environment and by standards imposed by structures on which the organization is dependent have an impact on the IT Governance mode choice. Mimetic pressures caused by peers, professional associations, or competitors also played an important role in IT Governance mode choice. Finally, normative pressures caused by inter-organizational networks and similar educational backgrounds also influenced the IT Governance choice.